Association between systemic rheumatic diseases and dementia risk: A meta-analysis - Wang, Yao-Chin; Lin, Muh-Shi; Huang, Abel Po-Hao; Wu, Chieh-Chen; Kung, Woon-Man (Frontiers in Immunology, 2022)
Background and Aims: Epidemiological studies have been conducted on the relationship between systemic rheumatic diseases (SRDs) and dementia. Therefore, we focused on determining the extent of alliances bounded by SRDs, along with the risk of dementia. Materials and Methods: Two independent reviewers assessed all studies retrieved from the PubMed, EMBASE, Scopus, and Web of Science databases between January 1, 2000 and November 30, 2021. Only observational studies that estimated the possibility of dementia in participants with SRD were considered. The random-effects model was applied to forecast pooled risk ratios (RRs) and 95% confidence intervals (CI). Heterogeneity among the studies was evaluated using the Q and I2 statistics. The quality of the included studies was assessed using the Newcastle-Ottawa Scale. Funnel plots were used to calculate the risk of bias. Results: Seventeen observational studies with 17,717,473 participants were recruited. Our findings showed that among the participants with SRDs, those with osteoarthritis, systemic lupus erythematosus, and Sjogren’s syndrome were highly related to an elevated risk of dementia (pooled RR: 1.31; 95% CI: 1.15–1.49, p<0.001; pooled RR: 1.43; 95% CI: 1.19–1.73, p<0.001; and pooled RR: 1.26; 95% CI: 1.14–1.39, p<0.001, respectively). However, participants with rheumatoid arthritis (RA) were not associated with an increased risk of dementia (pooled RR: 0.98; 95% CI: 0.90–1.07, p<0.001). Conclusion: This systematic review and meta-analysis demonstrated an increased dementia risk among SRDs participants, except for RA.